Limits of Islamism: ideological articulations of Jamaat-e-Islami in contemporary India and Bangladesh - Islam, M (2012)
My doctoral thesis analyses the political ideology of Islamism by taking the case study of a major Islamist organization, namely the Jamaat-e-Islami in contemporary India and Bangladesh. In doing so, I try to understand the similarities and differences of the ideological articulations of Islamism in a Muslim minority context of India and in a Muslim majority context of Bangladesh. The thesis is written from a political theory perspective in general and within the realm of ideology studies in particular. The study analyses how and why the Jamaat is responding to the economic and cultural issues of neoliberal India and Bangladesh. One cannot possibly ignore the neoliberal context within which Islamists are generating markedly new kinds of political articulations with an unprecedented set of political demands, never seen before in the history of Islamist movements. The ideological articulations of Jamaat have been studied by analyzing various primary sources—organisational literature, the party constitution, policy resolutions, press releases, election manifestos and political pamphlets of Jamaat-e-Islami. In addition, this dissertation has also relied on field interviews with the Jamaat leadership in India and Bangladesh. Magazines and internet sources have been also helpful for this study. My thesis analyses Islamist responses to neoliberalism by discussing the contrasting conditions of contemporary India and Bangladesh. In doing so, I conclude that in India, Jamaat is opposed to neoliberalism whereas in Bangladesh, it has a ambiguous character vis-à-vis neoliberalism. However, Islamists in both these countries are opposed to cultural issues like atheism, ‘blasphemous’ views, live-in relationships and homosexuality, which they construe as the products of ‘western cultural globalization’. In this respect, I try to analyse why the Islamists are opposed to ‘western cultural globalization’. Finally, I also explain how Islamism, as a politico-ideological project of populist mobilization is facing a crisis in contemporary India and Bangladesh.